Political Economy Comes Home: On the Moral Economies of Housing. (June 2018) - Alexander, Catherine; Bruun, Maja Hojer; Koch, Insa
Struggles over housing are one of the most pressing social, economic and political issues of our time. Yet questions over access to, plus the redistribution and maintenance of secure housing have only recently begun to be considered anthropologically. Drawing on E.P. Thompson's concept of moral economy, this special issue addresses these questions and considers how contemporary moral economies of housing play out. Citizens try to make their demands for adequate and safe housing heard, but such aspirations are often undermined by, political rhetoric, state officials, loan terms and the law. People claim allegiances to particular moral communities, thus (re)constituting themselves as deserving of secure tenure and proper homes, often in the face of stigma, laws or policies that construct them as the very reverse. By placing fine-grained ethnographic analysis in conversation with the political economy of housing, we redefine housing as an essentially contested domain where competing understandings of citizenship are constructed, fought over and acted out.